Using Artificial Intelligence to Improve Primary Care for Patients and Clinicians - Sarkar, Urmimala; Bates, David W (JAMA internal medicine, 2024)
This Viewpoint discusses how artificial intelligence can be used to increase efficiency of primary care processes for clinicians and patients.